If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -16 = 29 + -2x Reorder the terms: -16 + 7x = 29 + -2x Solving -16 + 7x = 29 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -16 + 7x + 2x = 29 + -2x + 2x Combine like terms: 7x + 2x = 9x -16 + 9x = 29 + -2x + 2x Combine like terms: -2x + 2x = 0 -16 + 9x = 29 + 0 -16 + 9x = 29 Add '16' to each side of the equation. -16 + 16 + 9x = 29 + 16 Combine like terms: -16 + 16 = 0 0 + 9x = 29 + 16 9x = 29 + 16 Combine like terms: 29 + 16 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| 3/x=3/4x+3 | | 2x+4+24=108 | | 4r-3+2r=3 | | 3x+2-x+x=x+6 | | n/4=17/3 | | 20e^8t=12e^5t | | 3x+6=45-5x-20 | | 9-1(x-5)=4 | | 5x+8=-9x+64 | | (xy+1)dx+x(x+4y-2)dy=0 | | 4-1/9x=10/3 | | -9=-3(x-3) | | j-8.4=25.2 | | 2(7)-9y=14 | | 11x+14=4x+56 | | (x^2)+9x=3cost | | 16x^2-4x-12=0 | | k^2-4k-12=0 | | 3(2-x)-3-x+4=2-x+5 | | -2x^2+3x-7=-9 | | 2x+6=24x+4 | | 2x^5+6x^2+8x=0 | | 5(8-2y)-2y=4 | | 9=4x-7/3 | | x/3+56=14 | | 2=+2x+13x+2x | | 60+10x=25x | | 2=+9x+13x+2x | | 4=+9x+13x+2x | | 2.3y-9.5=-9.7 | | -2x^2-2x=-3 | | 6x+9=-3+6x+12 |